1998
DOI: 10.1159/000014979
|View full text |Cite
|
Sign up to set email alerts
|

Dispensable and indispensable genes in an ameiotic fish, the Amazon molly <i>Poecilia formosa</i>

Abstract: All-female vertebrates are excellent model systems for studying many evolutionary problems. One of these is the Amazon molly. In this review, three aspects of its biology are discussed: (1) An important question is how dispensable genes, such as all male coding genes, evolve in this species. A number of studies found that most of these genes remain remarkably stable and functional. (2) The gynogenetic Amazon mollies have to live in sympatry with males of a gonochoristic species, because sperm are needed to tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 35 publications
(45 reference statements)
2
50
0
Order By: Relevance
“…The power of the statistical analyses used here may be lacking because sample sizes are relatively small. However, numerous studies have documented significant differences in these behaviors in these fishes using similar experimental protocols, sample sizes, and rank statistics (Schlupp et al 1991(Schlupp et al , 1994(Schlupp et al , 1998Foran and Ryan 1994;Ryan et al 1996, Ptacek and Travis 1997Schlupp and Ryan 1997;Kö rner et al 1999;Landmann et al 1999). This suggests that the similarity in male response to hybrid and gynogenetic females in this study is not an anomaly, but rather is consistent with male behavior observed in other studies for these two species.…”
Section: Male Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…The power of the statistical analyses used here may be lacking because sample sizes are relatively small. However, numerous studies have documented significant differences in these behaviors in these fishes using similar experimental protocols, sample sizes, and rank statistics (Schlupp et al 1991(Schlupp et al , 1994(Schlupp et al , 1998Foran and Ryan 1994;Ryan et al 1996, Ptacek and Travis 1997Schlupp and Ryan 1997;Kö rner et al 1999;Landmann et al 1999). This suggests that the similarity in male response to hybrid and gynogenetic females in this study is not an anomaly, but rather is consistent with male behavior observed in other studies for these two species.…”
Section: Male Preferencementioning
confidence: 99%
“…Based on this imperfection, some studies have concluded that the evolutionary persistence of gynogenetic P. formosa is the result of a host/parasite coevolutionary arms race (Schlupp et al 1991(Schlupp et al , 1994Schartl et al 1995b;Schlupp and Ryan 1997). In this context, attractiveness of gynogenetic females imposes selection on heterospecific males, favoring the evolution of stronger male mate discrimination that, in turn, imposes selection on the gynogenetic females to evolve an even greater ability to attract males (Schlupp et al 1991;Schlupp and Ryan 1996;Schlupp et al 1998). Hence, gynogenetic females have been dubbed ''Red Queens'' (Schlupp et al 1991) because they may be locked in a coevolutionary battle with heterospecific males to maintain their ability to obtain sperm.…”
mentioning
confidence: 99%
“…However, this may be a difficult argument to apply for many gynogenetic species complexes. The asexual and sexual species need to be very close relatives for sperm to trigger embryogenesis properly (Hubbs & Hubbs 1932;Schlupp et al 1998), and speciation in this case is argued to reflect a single hybridization event ( Turner 1982;Avise et al 1991;Schartl et al 1995) rather than a process of niche differentiation. There is also currently neither evidence of niche differentiation (Heubel 2004) nor differences in reproductive rates in the same environment (Schlupp 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As similar to other gynogenetic fishes [43][44][45], the triploid gynoform was also demonstrated to be originated from an ancient hybridization event, and the maternal and paternal species might be Carassius auratus and Cyprinus carpio respectively [46]. In comparison with gonochoristic crucian carp, the major difference between them is the mode of reproduction.…”
Section: Discussionmentioning
confidence: 85%